The Use of a Marketing Communication Strategy By English Cafe Semarang in Building Brand Awareness - Ida Hendriyani; Athiyah Salwa; Luthfy Purnanta Anzie (University of Surakarta, 2022)
The business world has overgrown, creating fierce competition among English course institutions in Indonesia. The marketing communication strategy becomes vital for these institutions in informing about the products and the brands to form market perceptions of the services offered and to build brand awareness. The success of a marketing communication strategy of a business can be measured by its brand awareness among the market audiences. English Café is an English course institution in Semarang City that has the concept of making a café a supporting tool and a convenient place for studying and practicing English. Our research aims to explore its marketing communication strategy and measure its brand awareness among the samples taken from Semarang citizens, including its students and others. The qualitative method is used in the analysis with a descriptive data presentation. The tools include observations, interviews, questionnaires, and documentation. The researcher found the data result, there were 43 respondents; 12 respondents recognized English Café as an English course institution in Semarang. It was called Top of Mind which had a percentage of 27.91%. They had built the Top of Mind level of brand awareness for English Café Semarang. The researcher found 22 respondents who recalled the English Café brand without the aid of recall when they needed the English Café course program. It was called Brand Recall which had a percentage of 51.17%. In the last finding, the researcher got 9 respondents who were unaware of the English Café brand as an English course institution in Semarang. It was called Unaware of Brand which had a percentage of 20.93%.